비알콜성 간경변증 환자에서 영양보충에 따른 영양개선의 효과 - 안수현(Ahn Su Hyun); 김오연(Kim Oh Yoen); 이종호(Lee Jong Ho); 김지영(Kim Ji Young); 한광협(Han Kwang Hyup) (Hanʼguk yongyang hakhoe chi, 2003)
Severe protein-calorie malnutrition, common in patients with advanced liver disease, can seriously undermine the capacity for regeneration and functional restoration of liver. Nutritional supplementation for these patients can improve biochemical and hormonal abnormalities. However, these effects were not identified in patient with nonalcoholic liver cirrhosis. To determine effects of nutritional supplementation in patients with nonalcoholic liver cirrhosis, 77 subjects aged 29 to 69 years participated in this study for 12 weeks and were subdivided into three groups; normal diet group (Control group, n ＝ 16), branched-chain amino acid supplementation group (BCAA group, n ＝ 31), nutritional supplementation group (NS group, n ＝ 30). Anthropometric parameters, hemoglobin, hematocrit, blood cell counts, serum levels of lipids, vitamins, minerals and fatty acid composition, and plasma amino acids were examined. The mean values of age and height, and the initial values of weight and body mass index (BMI) were not different among all groups. After 12 weeks, there were no significant changes in these values in Control group. Only NS group showed significant increases in weight, lean body mass, midarm circumference, triceps skinfold thickness. Serum transferrins were increased both in BCAA and NS groups. Plasma levels of branched-chain amino acids, urea amino acids and glutamic acid were also significantly increased in these groups, but plasma levels of ammonia, serum LDL cholesterol and atherogenic index were decreased. However, there were no significant changes in serum levels of vitamin and mineral and composition of fatty acids in phospholipids in these groups. These results showed that the nutritional supplementation for patients with nonalcoholic liver cirrhosis can more improve nutritional status in these people together with increases of weight, body fat and lean body mass, compared to only BCAA supplementation. To ascertain and investigate the appropriate nutritional supplementation for patients with nonalcoholic liver cirrhosis, further studies are necessary.